PENGARUH BOOK TAX DIFFERENCES, TINGKAT HUTANG DAN ALIRAN KAS OPERASI TERHADAP PERSISTENSI LABA - Sitorus, Faisal; Sari, Asih Purwana (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
The purpose of this study is to determine the effect of Book Tax Differences, Debt Levels and Operating Cash Flow on earnings persistence in the construction and building subsector companies on the Indonesia Stock Exchange. Variables in this study are Book Tax Differences, Debt Levels and Operating Cash Flow as independent variables and Earnings Persistence Variable as Dependent Variable. This research is a descriptive study with a quantitative approach. The population used in this study were all construction and building subsector companies listed on the IDX totaling 19 companies. The sample in this study was 14 construction and building subsector companies using purposive sampling method. The data used in this study are secondary data in the form of financial statements of the construction and building subsector companies in 2017-2020. While the data analysis used is the classical assumption test and hypothesistesting in logistic regression using SPSS. The results show that Book Tax Differences and Debt Levels do not affect Profit Persistence, while Operating Cash Flow has a positive effect on Profit Persistence.